Fight through cartoons my story of harassment, intimidation & jail - Zunar; Cheema, Sukhbir (Marshall Cavendish Editions, 2019)
This book chronicles Zunar's fight through cartoons from 2009 to 2018. Peppered within the pages of this book are some of Zunar's timeless philosophies on cartooning, which have kept him going despite the odds stacked against him - arrests, court charges, banning of books, travel ban. In this book, Zunar also sheds light on the methodological approach he utilises in his cartoons to effectively deliver his messages. From the conception of a cartoon right down to inking it, Zunar bares what goes on his mind when he draws these cartoons. From being labelled controversial to becoming an award winning cartoonist, this is Zunar's fight through cartoons in his own words.